2023
DOI: 10.1182/bloodadvances.2022009309
|View full text |Cite
|
Sign up to set email alerts
|

A validated composite comorbidity index predicts outcomes of CAR T-cell therapy in patients with diffuse large B-cell lymphoma

Abstract: Chimeric antigen receptor T-cell therapy (CART) has extended survival of patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL). However, limited durability of response and prevalent toxicities remain problematic. Identifying patients at high risk of disease progression, toxicity, and death would inform treatment decisions. Although the cumulative illness rating scale (CIRS) has been shown to correlate with survival in B-cell malignancies, no prognostic score has been independently validated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…At present, several study groups aim at optimizing the assessment of comorbidities with respect to the outcome of CAR‐T cell therapies 26–29 . Despite being associated with reduced PFS as highlighted in the present study and also shown by other analyses, 27,28 functional scores such as ECOG performance score do not capture comorbidities, and good performance scores are usually part of CAR‐T eligibility criteria in several countries 2,28 . Thus, given the already comparable outcomes for elderly patients, effective and easy‐to‐use assessment tools are needed to further optimize patient selection, particularly among older patients to further reduce toxicities.…”
Section: Discussionmentioning
confidence: 77%
“…At present, several study groups aim at optimizing the assessment of comorbidities with respect to the outcome of CAR‐T cell therapies 26–29 . Despite being associated with reduced PFS as highlighted in the present study and also shown by other analyses, 27,28 functional scores such as ECOG performance score do not capture comorbidities, and good performance scores are usually part of CAR‐T eligibility criteria in several countries 2,28 . Thus, given the already comparable outcomes for elderly patients, effective and easy‐to‐use assessment tools are needed to further optimize patient selection, particularly among older patients to further reduce toxicities.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, morbidities and their corresponding weighted scores listed in CCI were initially assigned and validated for predicting the 10-years mortality (12). CIRS is another comorbidity index that has been validated as a mortality predictor (13), and its e cacy to predict the prognosis of elderly patients with hematopoietic malignancy was recently reported (14,15). The OR in multivariate analysis, AUC values in ROC analysis, and mortality were higher in patients with the highest quartile of CIRS than those with the highest quartile of CCI.…”
Section: Discussionmentioning
confidence: 99%
“…[53][54] A recent study used the CIRS to define a prognostic score predictive of outcomes of CAR-T cell therapy in DLBCL patients. 55 Particularly, a CIRS 3 in the respiratory, upper gastrointestinal, hepatic, or renal system, defined as "severe 4", predicted shorter PFS and OS and a CRS of grade 3. 55 Therefore, a simplified CIRS-derived comorbidity index may predict adverse outcomes in DLBCL patients undergoing CAR-T cell therapy.…”
Section: Clinical Factors Vercellino and Coworkers Have Investigated ...mentioning
confidence: 99%